Interannual Variability of the Sulawesi Sea Circulation Forced by Indo‐Pacific Planetary Waves. Issue 3 (10th March 2019) - Hu, Xiaoyue; Sprintall, Janet; Yuan, Dongliang; Tranchant, Benoît; Gaspar, Philippe; Koch‐Larrouy, Ariane; Reffray, Guillaume; Li, Xiang; Wang, Zheng; Li, Yao; Nugroho, Dwiyoga; Corvianawatie, Corry; et al.
Abstract: The regional INDESO model configured in the Indonesian seas from 2008 to 2016 is used to study the mechanisms responsible for the variability of the currents in the Sulawesi Sea of the Indonesian seas. The model simulation compares reasonably with the seasonal to interannual variability of the moored current meter observations in the upper 350 m or so of the Maluku Channel during 2015 and 2016. The interannual variability of the currents in the eastern Sulawesi Sea in the model is found to be associated with both the Pacific and Indian Ocean remote forcing. Lag correlation analysis and a theoretical linear wave model simulation suggest that both the equatorial Kelvin waves from the Indian Ocean and the coastally trapped Kelvin waves from the western Pacific along the Philippine coast can propagate through the Indonesian seas and arrive at the Maluku Channel. In particular, from mid‐2015 to 2016 the Indian Ocean Kelvin waves are found to significantly impact the sea level anomaly variability in the Maluku Channel. The results indicate the importance of Indo‐Pacific planetary waves to the interannual variability of the currents in the Sulawesi Sea at the entrance of the Indonesian seas. Plain Language Summary: The Indonesian seas provide a tropical connection for the climate systems over the tropical Pacific and Indian Oceans, the dynamics of which are not clear so far. This study uses a high‐resolution computer model to simulate the currents measured by an acoustic current meter attached to a deep ocean mooring in the Maluku Channel of the northeastern Indonesian seas. Based on the successful simulation, the dynamics of the interannual variations of the circulation in the Maluku Channel are studied using the model and a simplified theoretical linear model. The interannual currents and sea level variability in the Maluku Channel are found to be affected by both the Indian Ocean Kelvin waves and the Philippine coastal Kelvin waves. It is found that the Indian Ocean Kelvin waves dominate the sea level variability in the Maluku Channel from mid‐2015 to 2016. In early 2015, the sea level variability in the Maluku Channel is dominated by the coastal Kelvin waves from the east Philippine coasts. The results are important for the understanding of the circulation at the entrance of the Indonesian seas and of the Indo‐Pacific interactions through the propagation of the planetary waves. Key Points: Current observations from a mooring in the Maluku Channel within the Indonesian seas are reproduced well by the INDESO high‐resolution model Interannual SLA variability in the Maluku Channel is affected by both Indian Ocean and Philippine coastal Kelvin waves SLA variability in the Maluku Channel is primarily forced by Indian Ocean Kelvin wave activity during 2015‐2016